Menurunkan frekuensi jajan tidak sehat pada anak dengan ID komorbid ADHD - Kokoh D. Putera (Universitas Muhammadiyah Malang, 2022)
Children with intellectual disability (ID) are susceptible to poor experiences of care and treatment outcomes, and this may compound existing health inequities. ID itself can has comorbidities with any other pathologies, such as attention deficit hyperactivity disorder (ADHD). Based on the assessment data, subject seems to be dependent to her parent, not able to sit quietly, and not able to understand long and complex instructions. Subject complained by her parent because of the high frequencies of snacking unhealthy beverages. Assessment methods were interviews, observation, Wechsler Intelligence Scale for Children (WISC), and Conner’s Parent Rating Scale – Revised (CPRS-R). The intervention given to overcome these problems was negative reinforcement. The results of the intervention showed that the behavior of snacking unhealthy beverages can be reduced.